PENGARUH MODEL LATIHAN TALI LENTUR DAN LUNGE DUMBBELL TERHADAP PENINGKATAN KETERAMPILAN RENANG GAYA BEBAS - Ida Soraya; Eko Hariyanto; Usman Wahyudi (Jurnal Pendidikan Jasmani)
Abstract: Purpose of this study to determine the effect of exercise flexible rope and dumbbell lunge toward increasing skills freestyle swimming. This type of research is true experiment (actual experiment), with  design of the pre-test post-test randomized control group design. The test results indicate that the hypothesis gained 7.21 F count> F table 4.41 for the pre-test and post-test group exercise flexible rope and dumbbell lunge, conventional exercise get results 0,036 <F table 4.41. So there is a significant relationship between exercise and the flexible rope with conventional exercise dumbbell lunge to the increased skills freestyleswimming.Keywords: Exercise Model flexible rope and Dumbbell Lunge, Freestyle Swimming skill Improvement.